The use of pesticides in agriculture in North-East Benin - DOGNON, Sèmanou Robert; Dognon, Hindé Reine; YOUSSAO ABDOU KARIM, ALASSANE; SCIPPO, Marie-Louise; YOUSSAO ABDOU KARIM, ISSAKA (My University, 2018)
In Benin, agriculture sector contributes to 26 % of the Gross Domestic Product in 2016. Intensification of agriculture has led to increase the use of new pesticides. This paper aims to asses practice attitudes of chemical pesticide use by farmers in North-East of Benin. Semi-structured interviews were conducted among 100 farmers chosen by the ‘‘snowball sampling’’ process in the communes of Banikoara, Kandi, Bembereke and Kalale. Survey was focused on farmer status, farming crops, pesticides and their use in agriculture. Descriptive statistics were performed with MS Excel while SAS software was used to perform chi-2 tests. Multiple correspondence analysis and hierarchical classification analysis were conducted to establish a farmer typology. Ninety-one percent of farmers were men and the predominant ethnic groups (p<0.01) were Bariba (31 %), Gando (29 %) and Mokole (23 %). Farmers were mostly uneducated (68 %) (p<0.001). The main activity of these farmers was agriculture (85 %) (p<0.001) before livestock (8 %) and trade (7 %).Surveyed farmers cultivated several crops of which maize (97.9±0.57 %), cotton (88.4±1.26 %) and sorghum (81.1±1.45 %) were predominant (p<0.01). Pesticides were mostly used to grow maize, cotton, sorghum and leguminous by 96, 94, 77 and 67 % of farmers, respectively. Thirteen herbicide active ingredients were found on labels of 21 chemical productswhile 14 active principles were found from 35 insecticide products. Seventy-eight percent of farmers purchased pesticides both in formal and illegal sectors while 17 % and 5 % of them shoped it from formal sector only and unauthorized market only, respectively. The modals of the pesticide use had sometimes known by 53 % of farmers. Farmers were classed in three groups: cluster 1 was high-risk class while clusters 2 and 3 were lower-risk classes able to cause contamination of environment and foods from animal bred in the study area by the pesticide residues. The use of pesticides as above described, suggests adverse health effects on farmers and on livestock animals.
Keywords: Pesticide; Agriculture; Survey; Benin